Morphological and molecular evidence for Osmundea coelenterata comb. nov. (Ceramiales, Rhodophyta) from the tropical Atlantic Ocean - Fujii, Mutue T.; Sentíes, Abel; Jover C., Abdiel; Díaz-Larrea, Jhoana; Areces, Arsenio (HIDROBIOLÓGICA, 2016)
Background. As part of the monographic studies on the Laurencia complex (Rhodomelaceae, Rhodophyta) from Cuba, detailed taxonomic research was carried out on Laurencia coelenterata, a diminutive species collected in Santiago de Cuba, in the eastern Cuban archipelago. The vegetative and reproductive features of the species clearly belong to the genus Osmundea, a member of the Laurencia complex: two pericentral cells per each vegetative axial segment, tetrasporangia cut off randomly from cortical cells, and filament-type spermatangial branches. Goals. In this study the morphological characteristics previously unknown to Laurencia coelenterata are shown, and in order that their taxonomic position within the Laurencia complex is discussed. Furthermore, the global geographic distribution of the Osmundea species is analysed. Methods. Morphological and molecular analysis of the rbcL gene sequences were performed allied with the preparation and interpretation of phylogenetic hypotheses. Results. The new morphological analysis of the paratype specimen (# 4451) housed in the Puertorriqueño Marine Herbarium showed that Laurencia coelenterata was incorrectly placed in the genus Laurencia. The phylogenetic position of the present species was inferred by the analysis of the chloroplast-encoded rbcL gene sequences, and the range of the genetic variation found in this analysis also supports the transfer of Laurencia coelenterata to the genus Osmundea, as O. coelenterata (D. L. Ballantine et Aponte) M.T. Fujii, Sentíes et Areces. Conclusions. The morphological and molecular approach in algal taxonomy is allowing consolidate the nomenclatural status of the species, and the new combination for Laurencia coelenterata as Osmundea coelenterata is not an exception.